Self-sustaining vortices in protoplanetary discs: setting the stage for planetary system formation - Regály, Zsolt; Kadam, Kundan; Dullemond, Cornelis (Monthly notices of the Royal Astronomical Society, 2021)
The core accretion scenario of planet formation assumes that planetesimals and planetary embryos are formed during the primordial, gaseous phases of the protoplanetary disc. However, how the dust particles overcome the traditional growth barriers is not well understood. The recently proposed viscous ring-instability may explain the concentric rings observed in protoplanetary discs by assuming that the dust grains can reduce the gas conductivity, which can weaken the magnetorotational instability. We present an analysis of this model with the help of GPU-based numerical hydrodynamic simulations of coupled gas and dust in the thin-disc limit. During the evolution of the disc the dusty rings become Rossby unstable and breakup into a cascade of small-scale vortices. The vortices form secularly stable dusty structures, which could be sites of planetesimal formation by the streaming instability as well as direct gravitational collapse. The phenomenon of self-sustaining vortices is consistent with observational constraints of exoplanets and sets a favourable environment for planetary system formation.
Gesehen am 18.11.2021